ЕКОНОМІЧНА СУТНІСТЬ ТА ФУНКЦІОНАЛЬНЕ ЗНАЧЕННЯ МАРКЕТИНГУ В МЕХАНІЗМІ УПРАВЛІННЯ ПІДПРИЄМСТВОМ - Kalinichenko, Olena (Zhytomyr Ivan Franko State University, 2025)
This article examines the modern economic environment, characterized by globalization and rapid digital transformation, which requires enterprises to transition from traditional marketing approaches to the use of flexible, integrated, and customer-oriented solutions. The success of any company is determined not only by its financial results, but also by the proper organization of marketing activities and the flexibility of the management system. In a market economy, marketing has become a fundamental element of the management system, ensuring not only sales, but also innovative development and social responsibility. Thus, marketing is not a separate department, but a philosophy of doing business. With this in mind, the main objective of the study is to identify the specific characteristics of managing a company's marketing activities and to justify priority ways of optimizing it in accordance with the challenges of modernity. The theoretical basis of the study is the works of leading domestic and foreign scientists (in particular, F. Kotler, J.-J. Lamben, L.V. Balabanova, A.O. Starostina, and others) devoted to the problems of marketing in the enterprise management mechanism. The analysis used methods of systemic and structural-functional analysis to determine the place of marketing in the corporate governance hierarchy, comparative analysis to classify marketing strategies (differentiation, low prices, digital marketing, content marketing, etc.), and logical generalization to form conclusions and recommendations. Particular attention was paid to analyzing the role of the marketing information system as a critically important tool for management decision-making. The article reveals that marketing plays a key coordinating role in the corporate governance system, ensuring the coordination of all departments based on a unified strategy aimed at creating unique consumer value. It was found that effective marketing management is characterized by multifactoriality (the transition from 4P to 7P/4C) and analytical orientation, which is confirmed by the growing importance of CRM systems, Big Data, and performance metrics (ROMI, LTV). It is argued that the strategic value of marketing lies in its ability to generate innovation and encourage companies to continuously update their product range. The key features of modern management are recognized as digital transformation, personalization of communications, the need to manage the brand as a strategic asset, and the critical importance of internal marketing for shaping a customer-centric culture. Taking these features into account, the main areas for optimization have been identified: the introduction of marketing automation tools, the integration of logistics and marketing, the development of staff competencies, and effective marketing risk management. The practical value of the results lies in the fact that the proposed improvement measures can be used by management personnel to diagnose and improve existing marketing management systems. The proposed classification of strategies and the identified key features of modern marketing (customer focus, interactivity, ecosystem) provide a roadmap for the transition to a more effective and adaptive management model.